Geography B geography for enquiring minds - Coles, Jo; Parkinson, Alan; Payne, Jo; Ross, Simon (Dynamic learning, 2020)
Written for the OCR GCSE (9-1) Geography B specification, this second edition provides new questions, case studies, content and fieldwork. Build your students' subject knowledge and cross-disciplinary enquiry skills with this modern, topic-based approach, brought to life through clear explanations and skills-focused activities. The updated case studies provide students with new, contemporary and engaging content for learners with an increased look at how human geography has changed such as trade development. New practice questions include increased opportunities for students to strengthen their exam skills particularly for interpreting and analysing geographical data. - Maps the content against the specification, providing an easy-to-follow teaching pathway designed by an author team of experienced teachers and examiners - Equips students with the subject knowledge and up-to-date case study examples they need to maximise their potential, with opportunities to undertake developmental activities for each topic - Offers you a whole-class solution to teaching the non-tiered papers with extension activities to stretch high achievers and scaffolded questions that support lower ability students - Embeds a focus on mathematical and statistical skills throughout by including opportunities to analyse a range of maps, graphs, GIS material and data sources - Prepares students to approach assessment confidently with practice questions of varying difficulty and handy tips for successfully answering enquiry questions - Highlights possible fieldwork projects and contains guidance on carrying out fieldwork, making it easier to integrate practical and theoretical learning.